The principal as a driver of quality: a systematic analysis of managerial competencies in improving non-academic achievement - Mundrikah, Siti; Senowarsito, Senowarsito; Maryanto, Maryanto (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the managerial competence of school principals in improving the quality of education and non-academic achievement through a Systematic Literature Review (SLR) approach. The study reviewed five articles published in SINTA journals from 2020 to 2023 using the PRISMA guidelines. The data were analyzed thematically based on the methods, instruments, and main findings of each study. The results show that all studies used a qualitative approach with instruments of interviews, observation, and documentation tested through data triangulation. Principals act as educators, managers, and motivators in managing school resources, designing coaching programs, and improving students’ academic and non-academic achievements. Supporting factors included collaboration between teachers and school committees, while the main obstacles were limited funds and infrastructure. Overall, the managerial competence of school principals was proven to have a significant effect on improving the quality of education. It is necessary to strengthen adaptive, collaborative, and innovative leadership capacities to build a sustainable school culture that is responsive to modern educational challenges.